The challenge of home and community older adult care in China: a survey of the capability of primary care physicians in providing geriatric healthcare services - Xiufang Chen; Kun Xie; Yahui Li; Dan Hu; Yong Chen; Jiaying Chen; Jiaying Chen; Jiaying Chen (Frontiers in Public Health)
IntroductionIn the context of ageing at home and in the community, healthcare services for older adult people in China are mainly provided by primary care physicians (PCPs). This study aimed to understand the level of geriatric healthcare service capability of PCPs in China and to give recommendations for improving care.MethodsWe surveyed PCPs in the eastern, central, and western regions of China, using a combination of multi-stage stratified cluster sampling and typical sampling. We evaluated the capability of PCPs in geriatric healthcare services in terms of diagnosis and treatment of common diseases, health management of the older adult, and health management of patients with chronic diseases. We compared the capability of PCPs in different regions, in urban and rural areas, and with different characteristics.ResultsWe found that Chinese primary care doctors had a low level of education and tended to be older in age. We also found a lack of general practitioners in China. Among the 8,469 respondents, 6,497 (76.7%) could diagnose and treat common diseases; 7,755 (91.6%) were capable of managing the health of the older adult, and 7,787 (91.9%) could manage the health of patients with chronic diseases.ConclusionResults indicated that China’s primary care physician workforce was of low quality. There were deficiencies in all competencies in geriatric healthcare services, and there were differences in capability between urban and rural areas. The findings suggest China’s primary healthcare services should be strengthened with targeted training and an emphasis should be placed on developing basic skills in geriatric healthcare services.